Lehren aus Corona Impulse aus der Wirtschafts- und Unternehmensethik - Hollstein, Bettina (Nomos Verlagsgesellschaft mbH & Co. KG, 2020)
Zusammenfassung Krisen wie die COVID-19-Pandemie sind für die Politik stets Anlass gewesen, festgefahrene Strukturen aufzubrechen und weitreichende Reformen umzusetzen. Pfadabhängigkeiten können in Krisenzeiten unterbrochen werden. Der vorliegende Band beleuchtet die gesellschaftlichen Auswirkungen der Pandemie sowie die langfristigen Herausforderungen und Potenziale, die mit ihr einhergehen, aus wirtschafts- und unternehmensethischer Perspektive. Wie verändert die COVID-19-Krise das Kräfteverhältnis zwischen Staat, Markt und Unternehmen? Welche Pflichten kommen auf Unternehmen während einer Pandemie zu? Inwieweit sind die Bekämpfung der Corona- und der Klima-Krise vereinbar? Welche Rolle kann und soll Wirtschaftsethik in Zeiten der Krise spielen? Mit Beiträgen von Prof. Dr. Michael S. Aßländer; Prof. Dr. Jörg Althammer; Prof. Dr. Martin Büscher; Niklas Dummer, M.A.; Dr. habil. Michael Ehret; Miriam Fink; Prof. Dr. Manfred Fischedick; Prof. Dr. Nils Goldschmidt; Prof. Dr. Hanns-Stephan Haas; PD Dr. Michaela Haase; Prof. Dr. Ludger Heidbrink; Prof. Dr. Ulrich Hemel; Prof. Dr. Lars Hochmann; Ruzana Liburkina, M.A.; Mark McAdam; Prof. em. Dietmar Mieth; Prof. Dr. Dr. Elmar Nass; Dr. Laura Otto; Prof. Dr. Reinhard Pfriem; Prof. Dr. Ingo Pies; Prof. em. Birger Priddat; Frauke Remmers; Dr. Bastian Ronge; Prof. Dr. Hartmut Rosa; Prof. em. Hermann Sautter; Dr. Philipp Schepelmann; Prof. Dr. Dr. Ulrich Schmidt; Prof. Dr. Markus Scholz; Prof. Dr. Andreas Suchanek; Prof. em. Peter Ulrich. Abstract Historically, crises such as the COVID-19 pandemic have prompted politicians to break up dead-locked structures and implement far-reaching reforms. Path dependencies can be interrupted in times of crisis. This volume examines the social impact of the current pandemic as well as both the long-term challenges it poses and the potential it offers from the perspective of economic and business ethics. How has the COVID-19 crisis changed the balance of power between the state, markets and business? What are the obligations of companies during a pandemic? To what extent are the fight against the coronavirus crisis and that against the climate crisis compatible? What role can and should business ethics play in times of crisis? With contributions by Prof. Dr. Michael S. Aßländer; Prof. Dr. Jörg Althammer; Prof. Dr. Martin Büscher; Niklas Dummer, M.A.; Dr. habil. Michael Ehret; Miriam Fink; Prof. Dr. Manfred Fischedick; Prof. Dr. Nils Goldschmidt; Prof. Dr. Hanns-Stephan Haas; PD Dr. Michaela Haase; Prof. Dr. Ludger Heidbrink; Prof. Dr. Ulrich Hemel; Prof. Dr. Lars Hochmann; Ruzana Liburkina, M.A.; Mark McAdam; Prof. em. Dietmar Mieth; Prof. Dr. Dr. Elmar Nass; Dr. Laura Otto; Prof. Dr. Reinhard Pfriem; Prof. Dr. Ingo Pies; Prof. em. Birger Priddat; Frauke Remmers; Dr. Bastian Ronge; Prof. Dr. Hartmut Rosa; Prof. em. Hermann Sautter; Dr. Philipp Schepelmann; Prof. Dr. Dr. Ulrich Schmidt; Prof. Dr. Markus Scholz; Prof. Dr. Andreas Suchanek; Prof. em. Peter Ulrich